Levelling the playing field : women's entrepreneurship as an egalitarian choice - Oppedisano, Jeannette M., 1943-; Fielden, Sandra L. (Women in management review, 2004)
Women in the UK frequently do not consider business ownership as an alternative to other forms of employment or as a means to gain economic benefits. The number of women currently entering in to businesses in the North of England is decreasing and is less than half of that in the South. This paper examines the preliminary findings from a longitudinal study exploring the socially created barriers to business start-up that inhibit the growth of women entrepreneurs and how they may be removed. The study employed an action research approach to investigate the experiences of UK women entering into.